Título Padrão: POESIA E TRADUÇÃO NO ENTRE-LUGAR LATINO-AMERICANO - Monteiro Pereira, Wagner (Revista de Letras, 2025)
This paper aims to consider the poetry and translation of Haroldo de Campos from the perspective of a transnational project undertaken by the author. In this sense, the conception of History and ideology in his work will be discussed, projecting translation as a mode of confluence between historical and ideological, which belongs to what the poet and essayist call transtemporality (Campos, 2013). In a second moment, the role of Hispanic-American literature in Haroldo's work and how the Baroque and Neo-Baroque (Campos, 2010) played a fundamental role in a poetic-critical turn in the last decades of the 20th century that the author experienced will be analyzed, based on approaches with authors such as Luis de Góngora, José Lezama Lima and Severo Sarduy, who help Haroldo, based on the idea of transculturation, to conceive his transcreation. Finally, how Galaxias (Campos, 2004) fits into a Latin American and transnational project based on the concept of Americanness and translation in different aspects will be examined.